PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN YANG DIMEDIASI OLEH EFIKASI DIRI PADA KARYAWAN BANK SYARIAH INDONESIA BANDA ACEH - Yulan Dari; Irma Suryani (Departemen Manajemen, 2023)
This study aims to determine the relationship between transformational leadership style and motivation on employee performance with self-efficacy as a mediation. Data obtained through a survey of 134 employees of KC Aceh Diponegoro Bank Syariah Indonesia (BSI). The analytical method used is Statistical Product and Service Solutions (SPSS). The results of the study found that transformational leadership style, motivation and self-efficacy directly affect employee performance. The results of the study also found that transformational leadership style also influenced the mediator variables, namely self-efficacy on the influence of transformational leadership style variables and motivation on employee performance.